1970
DOI: 10.1246/bcsj.43.1372
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Behavior of Low Valence Sulfur Compounds. V. Decomposition and Oxidation of Tetrathionate in Aqueous Ammonia Solution

Abstract: The decomposition and oxygen oxidation of tetrathionate in aqueous ammonia solution have been investigated. In the decomposition, thiosulfate, sulfate and sulfamate were formed through penta- and trithionate as intermediate compounds. The molar ratio of the products (SO42−+SO3NH2−)/S2O32− was roughly equal to 2/7, where 0.1n ammonia solution was used. The deficient use of ammonia made the solution neutral or weakly acidic and the precipitation of sulfur and the formation of higher polythionates were observed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In addition, in the thiosulfate leaching system, copper and ammonia are added to accelerate gold dissolution through the formation of copper (II) ammine complexes. However, a problem associated with the use of cupric ammine is that it accelerates the oxidation of thiosulfate to produce tetrathionate, which is also unstable and can be easily degraded into trithionate and thiosulfate [91][92][93][94][95], as presented in Equations (18) and (19 The degradation products of thiosulfate, particularly polythionates including trithionate and tetrathionate, will intensely compete with gold (I) thiosulfate complex for active sites in the resins, and low concentration of them in the leach solution will decrease gold loading capacity of the resins tremendously. Therefore, it is very necessary to minimize the generation of them in the leaching stage to ensure an efficient gold recovery from the pregnant thiosulfate solutions by the resin adsorption technique.…”
Section: The Competitive Adsorption Of Undesirable Anionsmentioning
confidence: 99%
“…In addition, in the thiosulfate leaching system, copper and ammonia are added to accelerate gold dissolution through the formation of copper (II) ammine complexes. However, a problem associated with the use of cupric ammine is that it accelerates the oxidation of thiosulfate to produce tetrathionate, which is also unstable and can be easily degraded into trithionate and thiosulfate [91][92][93][94][95], as presented in Equations (18) and (19 The degradation products of thiosulfate, particularly polythionates including trithionate and tetrathionate, will intensely compete with gold (I) thiosulfate complex for active sites in the resins, and low concentration of them in the leach solution will decrease gold loading capacity of the resins tremendously. Therefore, it is very necessary to minimize the generation of them in the leaching stage to ensure an efficient gold recovery from the pregnant thiosulfate solutions by the resin adsorption technique.…”
Section: The Competitive Adsorption Of Undesirable Anionsmentioning
confidence: 99%
“…Selenosulfate formed from the reaction between sulfite and Se(0) (reaction ) and possibly by the mechanism described in reaction is expected to behave similarly to thiosulfate in oxygen‐rich aqueous environments. The oxidation of thiosulfate in aqueous systems by oxygen is an extremely slow process with tetrathionate (S 4 O 6 2− ) and sulfate as the main end products (Aylmore & Muir, ; Naito, Shieh, & Okabe, ). However, free metal ions can catalyze the oxidation of thiosulfate to tetrathionate, trithionate, and sulfate (Aylmore & Muir, ).…”
Section: Discussionmentioning
confidence: 99%
“…Selenosulfate formed from the reaction between sulfite and Se(0) (reaction 2) and possibly by the mechanism described in reaction (6) ) and sulfate as the main end products (Aylmore & Muir, 2001;Naito, Shieh, & Okabe, 1970). However, free metal ions can catalyze the oxidation of thiosulfate to tetrathionate, trithionate, and sulfate (Aylmore & Muir, 2001).…”
Section: mentioning
confidence: 99%
“…In particular, an arrangement of 4 rows consisting of 16 electrodes, made out of stainless steel, was mounted on perimeter of the reactor wall. Thus, approximate resolution of the spatial reconstruction is roughly 2 cm 3 . Another tank of the same size was encased inside a rectangular plexiglass container to be filled with liquid of the same refractive index as the studied solution in order to eliminate visual distortions.…”
Section: Object Of Studymentioning
confidence: 99%
“…It is suggested that ammonia transports gold ions to bulk solution by being more strongly adsorbed on gold surface [2]. Oxygen is needed to recover copper (II) from copper (I) at a little expense of slow thiosulphate oxidation by molecular oxygen [3]. Overall mechanism of gold leaching with thiosulphate can be briefly summarized by the following reaction [4] …”
Section: Introductionmentioning
confidence: 99%